2020
DOI: 10.1186/s12885-020-07589-4
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-lambda (IFNL) germline variations and their significance for HCC and PDAC progression: an analysis of The Cancer Genome Atlas (TCGA) data

Abstract: Background Hepatocellular carcinoma (HCC) and pancreatic ductal adenocarcinoma (PDAC) are malignancies with a leading lethality. With reference to interferons (IFNs) known to mediate antitumor activities, this study investigated the relationship between germline genetic variations in type III IFN genes and cancer disease progression from The Cancer Genome Atlas (TCGA) data. The genetic variations under study tag a gain-or-loss-of-function dinucleotide polymorphism within the IFNL4 gene, rs368234815 [TT/ΔG]. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Therefore, the fact a large amount of IFN-l is produced by DCs in response to STING activation warrants further investigation in the realms of cancer immunotherapy. However, as the IFN-l locus has been shown to be polymorphic in a subset of cancer patients and patients suffering from infectious diseases (8,29,65,66), moving forward, polymorphisms and differences in IFN-l gene expression will need to be taken into account when considering clinical STING immunotherapeutic approaches (29,35,67,68).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the fact a large amount of IFN-l is produced by DCs in response to STING activation warrants further investigation in the realms of cancer immunotherapy. However, as the IFN-l locus has been shown to be polymorphic in a subset of cancer patients and patients suffering from infectious diseases (8,29,65,66), moving forward, polymorphisms and differences in IFN-l gene expression will need to be taken into account when considering clinical STING immunotherapeutic approaches (29,35,67,68).…”
Section: Discussionmentioning
confidence: 99%
“…Reading out IFNL genotypes from controlled access sequencing reads was performed as described previously [24]. In brief, whole-exome sequencing (WXS) reads of nonmalignant tissue (code 11A) or peripheral blood leucocyte (code 10A) were cut down to the region spanning the IFNL gene cluster (chr19: 39,230,000-39,300,000) by using the BAM slice tool.…”
Section: Reading Out Ifnl Genotypesmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC), the most commonly seen type of primary hepatic carcinoma, is one of the most commonly seen malignancies in clinical practice, and its related mortality ranks the third among malignant tumors ( 1 ). Most patients with HCC have no obvious symptoms at the early stage but are already in the middle and advanced stages when they are treated, and the overall prognosis is still poor ( 3 ). It was found that the great rate of cancer relapse and metastases was the main factor leading to unsatisfactory prognoses of HCC sufferers.…”
Section: Introductionmentioning
confidence: 99%